NEWLY RECORDED SPECIES OF MARASMIUS (AGARICALES, MARASMIACEAE) TO THE MYCOTA OF INDONESIA - Atik Retnowati; Dennis Edmund Desjardin (PTTI, 2022)
Six species of Marasmius newly documented in the mycota of Indonesia are reported from Java; M. tubulatus, M. aff. subruforotula, M. nigrobrunneus f. cinnamomeus, M. xestocephalus, M. grandisetulosus, and M. olaeocephalus. Those species belong to sections Sicci and Marasmius. Detailed morphological descriptions, photos, line drawings of micro-morphological features of each species and keys to species are provided with a brief discussion on their taxonomy.